The Appearance of Social Reality in The Dancer Ahmad Tohari by Rene’ TA Lysloff - Noer Doddy Irmawati; Adhe Puspita Mayasari (Abjadia, 2021)
This study aimed to describe social reality in Dancer Dukuh Paruk by Ahmad Tohari using sociology of literature theory. Analyzing the data used descriptive method, and collected bylibrary study with identifying novel “The Dancer”. From this study can be seen that there is a social reality in Dukuh Paruk. Dukuh paruk is a poor village and backward in every way. In it there are traditions that may be considered by some as taboo and violating norms, but in the village of Dukuh Paruk, they are still strong in holding onto these traditions. The social condition of people who are poor in wealth and knowledge has other social impacts. Rasus and Srintil, who are the main characters in the novel, make Dukuh Paruk village a witness to their love journey which is full of problems and challenges. However, the social problems that hinder them are not only due to their inability to unite their love, but also because of the many environmental factors that surround them. In Dukuh Paruk village, there are many social realities which represent the life of Dukuh Paruk Village which is small but has complex problems. This phenomenoncaused by some aspects such aspoverty and lack of knowledge in society. Some social reality founded in this story started from poverty, sorcery, tyranny, love, prostitution, pre-wedding sex, trickery, social jealousy and sexual abuse.